Development of a Water Resources Distribution and Management Tool (SPEHR); Applied (2018)
Water management is a complex problem that relates to human and physical variables that are very hard to predict, there is a cultural and social and human driven variables (Agricultural practices, Cities growth and others) that are hard to capture into the complex interactions of the water allocation and the hydrological system. This research presents a new novel yet simple system that integrates information from river basin social and hydrological variables in an online system for decision support. The concept developed so far represents the Magdalena river system in Colombia, and allows to simulate and to share ideas. A communication bar includes a score of goodness provided by decision makers such that a level of agreement between actors can be achieved. Aside of this, the system is made open source such that other river basin can be set up and even other hydrological modelling systems can be plugged in.